Iamblichus on the Soul - Afonasin, Eugene (SCHOLE, 2010)
The Letters by the Neoplatonic philosopher Iamblichus of Chalchis (c. 242–325 ce), preserved in a fragmentary form by John of Stobi in his Antologia and translated into Russian in the previous issue of the journal (ΣΧΟΛΗ 4. 1 (2010) 166–193), are now supplemented by two minor testimonia (by Olympiodorus and Damaskius) and a note on the descend of souls in Later Neoplatonism.